Tata Kelola Kolaboratif untuk Mitigasi Rabies di Kabupaten Timor Tengah Utara - Hendrikus Hironimus Botha; Yohanes Imanuel Naif; Pionisius Minggu (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This study examines government collaboration in preventing and managing rabies in North Central Timor Regency. A descriptive qualitative approach is employed, utilizing the Collaborative Governance process framework developed by Ansell and Gash, which encompasses five stages: Initial Conditions, Facilitative Leadership, Institutional Design, Collaborative Process, and Intermediate Outcomes. The findings reveal that while the government has established a Command Post for Emergency Handling of Rabies Outbreaks as part of its collaborative efforts, significant challenges remain. Key weaknesses include insufficient alignment in the incentive distribution mechanisms for joint working groups and limited collaborative activities among agencies and institutions involved in the Rabies Disease Handling Command Post. These shortcomings hinder the full realization of Collaborative Governance objectives, specifically reducing rabies cases among animals and humans. The study underscores the necessity of developing technical guidelines for equitable incentive distribution and designing integrated activities that actively engage all stakeholders in rabies management. These measures are critical to achieving the intended outcomes of the Collaborative Governance process.